(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Tourism plays a significant role in today’s modern economic structure and is been a key driver in social progress. This sector has been identified as the only sector that involves a majority percentage of populace, directly or indirectly, for earning a decent livelihood. This reflects the fact that the tourism is fast turning into a volume game where an ever-burgeoning number of participants are pushing up revenues of industry players (hotels, tour operators, airlines, shipping lines, etc) and thus offers an interesting investment opportunity for long term investors. In this paper we through a light on the service provider perceptions on various parameters relating to their satisfaction on their revenue, Eco tourism and its sustainability. Primary data was collected from 379 Service providers, the data was analysed and the findings and suggestions were made.